First Principles Study of Cerium Monochalcogenides - Recep Eryiğit (Advances in Condensed Matter Physics)
A theoretical investigation of structural, magnetic, electronic, and lattice dynamical properties of cerium monochalcogenides using the generalized gradient approximation (GGA) + U within ultrasoft pseudopotentials and a plane-wave basis is presented. All the calculated quantities, except the local magnetic moments, are found to be in good agreement with the experimental data. The lattice dynamical results indicate a strong chalcogenide dependence for the anomalous features of the phonon dispersions.